PELATIHAN PENGOLAHAN SAMPAH ORGANIK MENJADI ECO ENZYME BAGI MAHASISWA AKADEMI KOMUNITAS NEGERI (AKN) REJANG LEBONG, BENGKULU - Sofian Sofian; Neny Rochyani; Indah Anggraini Yusanti; Fitra Mulia Jaya; Rih Laksmi Utpalasari; Riya Liuhartana (Jurnal Abdi Insani, 2023)
Eco enzyme is one of the potential organic waste processing technologies in the future. This community service activities aims to educate community groups ini managing organic waste produced by households into liquid fertilizer products that have economic value. The implementation method is carried out face to face by delivering materialand brochures as well as direct demonstrations of making eco-enzyme. The materials used are household waste such as vegetable and fruit that are not suitable for concumption, sugar/molase and water with a ratio of 3:1:6. The result of this activity is the increased understanding of participant in the management of organic waste originating from household. Participants showed good response, acceptance and participation during the activity. Participant are able to produce their own eco-enzyme as a natural disinfectant that can be used for households, agriculture or animal husbandry.